Professional Windows Embedded Compact 7 - Phung, Samuel, 1960- (Programmer to programmer., 2011)
Learn to program an array of customized devices and solutions As a compact, highly efficient, scalable operating system, Windows Embedded Compact 7 (WEC7) is one of the best options for developing a new generation of network-enabled, media-rich, and service-oriented devices. This in-depth resource takes you through the benefits and capabilities of WEC7 so that you can start using this performance development platform today. Divided into several major sections, the book begins with an introduction and then moves on to coverage of OS design, application development, advanced application developm.